The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1080/02652030500309319
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A: Potential epigenetic mechanisms of toxicity and carcinogenicity

Abstract: Assessment of the significance to human health of ochratoxin A (OTA) in food is limited by a lack of human toxicity data. Therefore, OTA risk evaluation relies mainly on the use of animal data, with renal carcinogenicity in rat being considered as the pivotal effect. The elucidation of the mechanism of action would improve the use of the carcinogenicity data for risk assessment. Direct genotoxicity versus epigenetic mechanisms appears to be a key question. In this presentation, new biochemical and toxicogenomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
1
19
0
3
Order By: Relevance
“…Russo et al (2005) found that human fibroblasts treated with OTA for 72 h (6-50 μM) exhibit an exposure time-dependent increase in the percentage of damaged DNA. This study also suggested the involvement of oxidative stress (due to an increase in ROS) in the OTA genotoxicity, which is also consistent with the work of Schilter et al (2005) and Zheng et al (2013). This finding is further supported by a study conducted by Kamp et al (2005) in the V79 and CV-1 cell lines and in primary rat kidney cells, which revealed a slight increase in the basic DNA damage (per cent of DNA) without treatment with DNA repair enzymes (formamidopyrimidine-DNA glycolyase and endonuclease III) in both cell lines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Russo et al (2005) found that human fibroblasts treated with OTA for 72 h (6-50 μM) exhibit an exposure time-dependent increase in the percentage of damaged DNA. This study also suggested the involvement of oxidative stress (due to an increase in ROS) in the OTA genotoxicity, which is also consistent with the work of Schilter et al (2005) and Zheng et al (2013). This finding is further supported by a study conducted by Kamp et al (2005) in the V79 and CV-1 cell lines and in primary rat kidney cells, which revealed a slight increase in the basic DNA damage (per cent of DNA) without treatment with DNA repair enzymes (formamidopyrimidine-DNA glycolyase and endonuclease III) in both cell lines.…”
Section: Discussionsupporting
confidence: 91%
“…Two hypotheses are still discussed when dealing with the carcinogenicity of OTA. The first hypothesis suggests that the carcinogenicity of OTA is linked to its epigenetic nature because OTA produces effects in target cells that either indirectly lead to neoplasic transformation or facilitate the development of neoplasms from cytogenetically transformed cells (O'Brien and Dietrich, 2005;Schilter et al, 2005;Turesky, 2005). The second hypothesis suggests that its carcinogenicity is due to genotoxic mechanisms (Hibi et al, 2013a(Hibi et al, , 2013bManderville, 2005;Mantle et al, 2010;Pfohl-Leszkowicz and Castegnaro, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Likewise, such accompanying OTA effects might largely be absent in liver even at dosages that already drive tumor formation in the kidney. Although this is still highly speculative and needs further confirmation, it is noteworthy that Schilter et al [52] have presented evidence that OTA given chronically to rats mediates totally different responses in kidney and liver with respect to altered gene expression profiles. Disruption of pathways regulated by the transcription factors hepatocyte factor 4 alpha (HNF 4 alpha) and nuclear factor-erythroid 2-related factor (Nrf2) was observed in kidney but not in liver.…”
Section: Resultsmentioning
confidence: 92%
“…In a variety of animal models OTA has produced a wide array of toxicological effects, including nephrotoxicity, nephrocarcinogenicity, neurotoxicity, and immunotoxicity (17,18).…”
Section: Ochratoxin A: a Hazardous Mycotoxinmentioning
confidence: 99%
“…Numerous studies have tried to elucidate the mechanisms implicated in OTA toxicity (9,17,19). The OTA molecule consists of a dihydroisocoumarin moiety that is amide-linked to the L-phenylalanine moiety ( Figure 1) which is a structural analogue of phenylalanine (Phe).…”
Section: Ochratoxin A: a Hazardous Mycotoxinmentioning
confidence: 99%